Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/brainsci12080959
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to Stimulant Medication for Attention Deficit Hyperactivity Disorder: Literature Review and Case Report

Abstract: Recommended treatment for attention deficit hyperactivity disorder (ADHD) includes stimulant medication. While these medicines are effective for most ADHD patients, benefits may wear off, suggesting tolerance. This paper reviews the published literature on tolerance to stimulant medication treatment for ADHD. As there are relatively few studies published, pivotal studies and ADHD treatment guidelines were also reviewed. Research demonstrates physiological changes related to continued stimulant usage in neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, inconsistent doses, unconventional ROAs, or combination with other substances probably increase the risk for serious outcomes, including fatalities (Farquhar et al , 2002; Ruwald et al , 2012; Hay et al , 2015; Faraone et al , 2020; Kariisa et al , 2021). The combination with benzodiazepines often used to intensify recreational experiences or reduce unwanted side effects (Grimsrud et al , 2019), and especially the co-use of opioids increases the risk of fatality (UNODC, 2021) as shown for the latter for cocaine and other psychostimulants with abuse potential (Kariisa et al , 2021). Unexpectedly, our study found similar proportions of intravenous administration in fatal and nonfatal cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, inconsistent doses, unconventional ROAs, or combination with other substances probably increase the risk for serious outcomes, including fatalities (Farquhar et al , 2002; Ruwald et al , 2012; Hay et al , 2015; Faraone et al , 2020; Kariisa et al , 2021). The combination with benzodiazepines often used to intensify recreational experiences or reduce unwanted side effects (Grimsrud et al , 2019), and especially the co-use of opioids increases the risk of fatality (UNODC, 2021) as shown for the latter for cocaine and other psychostimulants with abuse potential (Kariisa et al , 2021). Unexpectedly, our study found similar proportions of intravenous administration in fatal and nonfatal cases.…”
Section: Discussionmentioning
confidence: 99%
“…The MPH-induced dopamine signaling affects the reward system and, especially when administered via the nasal or intravenous route, leads to euphoric effects and 'highs' similar to cocaine (Morton and Stockton, 2000;Volkow et al, 2002). Although the development of tolerance to MPH is not yet fully understood, it may probably be caused by the upregulation of dopamine transporters in the striatum (Volkow et al, 2012;Taylor, 2019;Handelman and Sumiya, 2022). Dependence and withdrawal symptoms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1 ADHD is considered a chronic condition, and many individuals diagnosed in childhood continue to experience symptoms and functional impairment as adults. 3 Traditional pharmacological interventions and behavioral therapy for ADHD may have potential negative effects, as seen with Dextromethorphan (DM) and its impact on ADHD symptoms. 2 While these treatments show efficacy in many cases, their therapeutic benefits may diminish over time, leading to tolerance development.…”
Section: Introductionmentioning
confidence: 99%
“…Medication and behavioral treatment are frequently used, with 62.0% of children with ADHD receiving medication and 46.7% receiving behavioral treatment 1 . ADHD is considered a chronic condition, and many individuals diagnosed in childhood continue to experience symptoms and functional impairment as adults 3 . Traditional pharmacological interventions and behavioral therapy for ADHD may have potential negative effects, as seen with Dextromethorphan (DM) and its impact on ADHD symptoms 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation